Identification of the first gestational ground for tiger sharks (Galeocerdo cuvier) in the Central Indian Ocean using a high-definition submersible ultrasound - Sulikowski, James A.; Perisic, Nathan; Askin, Arzucan; Vossgaetter, Lennart; Bocchi, Filippo; Hussain Ali Didi, Hamna; Inah, Ahmed; Ivanova, Tatiana (Frontiers in Marine Science, 2024)
The reproductive state of wild, free-swimming tiger sharks (Galeocerdo cuvier), was assessed using underwater ultrasonography at a diving site in Fuvahmulah, a Maldivian atoll within the central Indian Ocean. The presence of embryos were observed in 93% of the adult sharks (26/28) and two distinct embryonic size groups were observed within the subset of scanned adult females. The results suggest that the observed dive site functions as a gestation ground and builds upon previous work that emphasizes the importance of dive sites for the collection of biological data for shark conservation and management.